Palestinian Nursing Students' Perspective of Clinical Decision-Making - Mohammad Faisal Al Ali RN, MSN (SAGE Publishing, 2024)
Introduction One of the most important aspects of nursing education and practice is clinical decision-making (CDM), which is also crucial to clinical competency. Objective The study aimed to assess the CDM of undergraduate nursing students by using the CDM nursing scale. Method The study was cross-sectional and involved 315 nursing student participants. Data collection utilized the Clinical Decision-Making Scale, which comprises domains such as "canvassing of objectives and values," "search for alternatives or options," "evaluation and reevaluation of consequences," and "search for information and unbiased assimilation of new information." Statistical analyses included Pearson correlation, ANOVA, and independent t -tests. Data collection occurred during the second semester of 2023. Results The results indicated that the mean age of the students was 21.69 ( SD  = 1.6) years. In terms of gender, the majority were males, constituting 216 (68.6%) of the participants. Among the participants, 105 (33.3%) were from the second year, 108 (34.3%) from the third year, and 102 (32.4%) from the fourth year. The analysis revealed that the average CDM score was 129.8 ( SD  = 17.5). Additionally, examination of the subscales of CDM showed that the highest subscale score was for "search for information and unbiased assimilation of new information" ( M  = 33.1, SD  = 5.3), while the lowest subscale score was for "search for alternatives or options" ( M  = 31.8, SD  = 6.0). Furthermore, the analysis demonstrated a significant difference between academic year level and the mean CDM scores ( p  < .05), along with a positive relationship between the CDM score and students' age ( r  = .67, p  = .001). Conclusion The findings revealed that nursing students exhibit a moderate level of CDM. Moreover, it was revealed that students' CDM is influenced by both their age and academic year level.